Mendelian Randomization Analysis Reveals Causal Effects of the Human Gut Microbiota on Abdominal Obesity. Issue 6 (24th March 2021) - Xu, Qian; Zhang, Shan-Shan; Wang, Rui-Rui; Weng, Yu-Jing; Cui, Xun; Wei, Xin-Tong; Ni, Jing-Jing; Ren, Hai-Gang; Zhang, Lei; Pei, Yu-Fang
Abstract: Background: Although recent studies have revealed an association between the composition of the gut microbiota and obesity, whether specific gut microbiota cause obesity has not been determined. Objectives: The aim of this study is to determine the causal relationship between specific gut microbiota and abdominal obesity. Based on genome-wide association study (GWAS) summary statistics, we performed a 2-sample Mendelian randomization (MR) analysis to evaluate whether the gut microbiota affects abdominal obesity. Methods: Gut microbiota GWAS in 1126 twin pairs (age range, 18–89 years; 89% were females) from the TwinsUK study were used as exposure data. The primary outcome tested was trunk fat mass (TFM) GWAS in 492, 805 participants (age range, 40–69 years; 54% were females) from the UK Biobank. The gut microbiota were classified at family, genus, and species levels. A feature was defined as a distinct family, genus, or species. MR analysis was mainly performed by an inverse variance–weighted test or Wald ratio test, depending on the number of instrumental variables (IVs) involved. A sensitivity analysis was performed on significant results by a weighted median test and a weighted genetic risk score (GRS) analysis. Results: Results of MR analyses provided evidence of a causal association between 3 microbiota features and TFM, including 1 family [ Lachnosiraceae ; P  = 0.02; β = 0.001 (SEE, 4.28 × 10 −4 )], 1 genus [ Bifidobacterium ; P  = 5.0 × 10 −9 ; β = −0.08 (SEE, 0.14)], and 1 species [ Prausnitzii ; P  = 0.03; β = −0.007 (SEE, 0.003)]. Both the weighted median test and GRS analysis successfully validated the association of the genetically predicted family, Lachnosiraceae ( P weighted median  = 0.03; P GRS  = 0.004). Conclusions: Our findings provided evidence of a causal association between gut microbiota and TFM in UK adults and identified specific bacteria taxa that may regulate the fat metabolism, thus offering new direction for the treatment of obesity.